El conejo europeo (Oryctolagus cuniculus): un nuevo invasor en el Parque Nacional Nahuel Huapi - Galende, Gladys; Pozzi, Carla; Montes de Oca, Fernanda
The European rabbit is a native species of southern Europe and northern Africa which was introduced in many countries and is considered among the most harmful in the world. In Argentina the rabbit is an invasive species that was established in the center and south of the country and there is a high probability of invasion across the Patagonian region. Considering these antecedents, the objective of this study was to confirm the early presence of European rabbit and determine the habitats occupied in northern PNNH. In an annual cycle, we conducted seasonal surveys searching indicators of activity and confirmed the presence of rabbit, by their fecal pellets in three typical habitats: a) mallín b) shrubland c) Nothofagus antarctica. The results confirmed the presence of rabbit and their progress at sites located close to the route of the Seven Lakes in the northern boundary of PNNH. The pellet densities were low and in the winter when the eruption Puyehue volcano occurred, did not record their presence; even in the spring again to observe their activity. While the abundance was low, this result should be considered with caution as permanence, and numerical recovery of this herbivore, after volcanic event, highlights its great ability to survive, even in conditions of low availability of food. Early detection of this invasive species will take urgent decisions considering the ecological consequences of their presence in order to prevent its spread. Fil: Galende, Gladys. Universidad Nacional del Comahue. Centro Reg.universidad Bariloche. Departamento de Zoologia. Catedra de Vertebrados; Argentina Fil: Pozzi, Carla. Administración de Parques Nacionales. Parque Nacional "nahuel Huapi"; Argentina Fil: Montes de Oca, Fernanda. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina